Various methods affect the flexural strength of repairing the denture base - Alfahdawi, Ibrahim H. (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: The assembly of replacement teeth to mimic natural ones remains a challenge for dentists, particularly regarding the surface characteristics of prosthetic teeth. Purpose: To evaluate various surface mechanical techniques that affect the flexural stress of a repaired denture base. Methods: Six sets (n = 10) of sixty heat-polymerized acrylic resin bar-shaped samples have been produced. Samples were divided into halves to give a 1-mm clearance, with the exception of the group under positive control (group PC). Also taken into account was a negative control group (group NC) that received no skin treatment. Other groups received a variety of surface treatments, including group Er:YAG laser therapy, group abrasion by airborne particles (APA), group APA + Laser, and group Bur grinding. All sectioned samples were repaired by auto-polymerizing acrylic resin, which was then thermocycled after surface roughness was measured with a profilometer. A global testing device conducted a three-point bending test. Results: The mean surface roughness of all study groups was considerably greater than group NC's (P<0.05). With the exception of group Bur, group PC's flexural strength was considerably greater than that of all other groups (P=0.999). The bending strength of groups Bur and Laser among all surface-treated groups was significantly greater than that of group NC (P=0.001 and P=0.015, respectively). Conclusion: All surface treatments enhanced surface roughness in comparison to the untreated group, but bur grinding and Er:YAG laser exposure also significantly raised the flexural strength of the sectioned groups. Sectioned polymethyl methacrylate’s flexural strength was significantly increased by bur grinding.